An exploratory study on customer perception of solo dining - de Quiroz, Ma. Geanelli A.; Ulvida, Princess Jazmine S.
In the Philippines, eating together is a fundamental part of socialization and celebration, which mirrors how collectivist the nation is, where family bonds and group relationships are sought (Shapiro, n.d.). This cultural backdrop makes solo dining an intriguing yet unexplored phenomenon (Ay-ay & Uy, 2014). Through the influence of different Asian countries on the Philippines, some of their foodways have already been adapted in the country. Among these foodways is the emergence of solo dining restaurants. (Dickens, 2018). This study aims to analyze the perceptions of the customers on solo dining restaurants set up and its effects on the behaviors of Filipino customers. In particular, restaurants located within the Luzon area of the Philippines, the region with a diverse and rapidly evolving dining scene. This region has a higher concentration of fast-casual dining establishments, making it an ideal location to explore solo dining experiences (Cua, 2020). To achieve this objective, an exploratory analysis was conducted. A total of 150 solo dining restaurant customers were surveyed online through Qualtrics survey forms posted on social media platforms such as Facebook and Instagram. Findings revealed that all six dimensions of the DINESCAPE, namely the facility aesthetics, ambience, lighting, layout, table setting and placement, and service personnel, contribute to the overall accommodation of solo diners, with layout showing the greatest influence, particularly through interior arrangements and spaciousness. In contrast, table settings and layout were the least impactful. These results demonstrated a positive relationship between the physical attributes of the solo dining setup and the customers emotional state, as most of the respondents felt happy and pleased during their dining experience. Lastly, the solo dining experience notably influences the customer's likelihood to recommend the restaurant to peers.